2016
DOI: 10.1016/j.envres.2016.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to organophosphate and carbamate pesticide use during pregnancy, poverty during childhood, and cognitive functioning in 10-year-old children

Abstract: Background Low-income communities and communities of color have been shown to experience disproportionate exposure to agricultural pesticides, which have been linked to poorer neurobehavioral outcomes in infants and children. Few studies have assessed health impacts of pesticide mixtures in the context of socioeconomic adversity. Objectives To examine associations between residential proximity to toxicity-weighted organophosphate (OP) and carbamate pesticide use during pregnancy, household- and neighborhood-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 49 publications
2
44
2
4
Order By: Relevance
“…In this cohort, we previously reported associations between Full-scale IQ at 7-years of age and prenatal OP insecticide use within 1 km of maternal residences during pregnancy (Gunier et al, 2016; Rowe et al, 2016) and also with other potentially neurotoxic pesticides including carbamates, neonicotinoids, pyrethroids and maneb (Gunier et al, 2016). A study utilizing California PUR data observed higher odds of autism spectrum disorder (OR = 1.6; 95% CI: 1.0 – 2.5) with any use of OP insecticides within 1.5 km of their residence during the prenatal period (Shelton et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this cohort, we previously reported associations between Full-scale IQ at 7-years of age and prenatal OP insecticide use within 1 km of maternal residences during pregnancy (Gunier et al, 2016; Rowe et al, 2016) and also with other potentially neurotoxic pesticides including carbamates, neonicotinoids, pyrethroids and maneb (Gunier et al, 2016). A study utilizing California PUR data observed higher odds of autism spectrum disorder (OR = 1.6; 95% CI: 1.0 – 2.5) with any use of OP insecticides within 1.5 km of their residence during the prenatal period (Shelton et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…A study using PUR data showed that methyl bromide use within a 7 × 7 square mile area (∼8 kilometer radius) around monitoring sites explained 95% of the variance in methyl bromide air concentrations, indicating a direct relationship between nearby agricultural use and potential community exposure (Li et al, 2005). Several epidemiologic studies have used PUR data and observed associations between higher nearby agricultural pesticide use during pregnancy and adverse neurodevelopmental outcomes including birth defects (Carmichael et al, 2014; Rull et al, 2006; Yang et al, 2014), autism (Roberts et al, 2007; Shelton et al, 2014) and cognitive function (Gunier et al, 2016; Rowe et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Working memory is the ability ‘to hold information in mind and mentally work with, while this information is not accessible by a sensory apparatus at that moment’ ( Diamond, 2013 , p. 142). The majority of research on working memory and poverty has been conducted on children, revealing that living in poverty causes significantly worse working memory ( Tine, 2014 ; Pavlakis et al, 2015 ; Rowe et al, 2016 ). From a biological perspective, this may be the result of reduced hippocampal development often associated with low socioeconomic status ( Pavlakis et al, 2015 ).…”
Section: Poverty and Executive Functionsmentioning
confidence: 99%
“…Our findings also imply that studies investigating the neurodevelopmental effects of current-use agricultural pesticide exposures should analyze the pesticide mixtures as a whole, rather than using the more conventional single pollutant models typically applied [12,13,41,62,63], as such methods are unable to control for the influence of other covarying pesticides. …”
Section: Discussionmentioning
confidence: 98%
“…We selected FSIQ as our outcome since our previous studies show consistent associations between FSIQ and prenatal urinary DAPs [11] and prenatal residential proximity to reported agricultural pesticide use [12,41]. A single bilingual psychometrician conducted all assessments.…”
Section: Methodsmentioning
confidence: 99%